Lesson design and development using the Costa Rican Mathematics curriculum - Hernández-Solís, Luis Armando (Innovaciones Educativas, 2020)
Problem solving has been incorporated in different ways into the curricula of various countries. In Costa Rica, it is placed as the main focus of the national curriculum with a methodological character that guides classroom action and structures the lesson. The article describes the design of two mathematical tasks formulated in a geometric problem the educational purpose of which is the introduction of the concept of bisector and its associated property. An analysis of the activation of mathematical processes is carried out for each task to then counter them with the evidence collected when applying the problem to a group of first year of secondary education of the Professional Technical High-School of Pacayas, Cartago, Costa Rica. Also, a global balance is made of how the lesson develops to assess if the problem posed fulfilled the previously established educational purposes. The conclusion is that the study offers the educational community a successful experience in the design and execution of a lesson framed in the problem-solving approach for learning new knowledge, in accordance with the study programs of the Ministry of Public Education of Costa Rica. MEP (2012).